Pengetahuan Siswa SMA Labschool UPGRIS Kota Semarang Tentang Pencegahan Demam Berdarah Dengan Wolbachia - Suharyo Suharyo; Yuniar Martha Musyafira (Pusat riset dan Inovasi Nasional, 2023)
Dengue fever remains a serious public health issue at the international and local levels, particularly in Semarang. Dengue fever can be controlled by Wolbachia bacteria, to suppress Aedes Sp. The SMA Labschool UPGRIS Semarang City students have never received instruction on controlling dengue disease using Wolbachia. This activity aims to increase the pupils' understanding of the issue. Powerpoint slides are used to facilitate discussions and the presentation of material during activities. There were 49 students in attendance. The Pre-Post test is used to measure knowledge. The non-parametric Wilcoxon sign rank test was used for a descriptive and analytical analysis of the measurement results. The findings indicate that 42 students' knowledge (85.7%) grew due to exposure. In the pre-test, students' understanding of dengue fever and how to control it using Wolbachia was, 50% complete (mean 50.6), but in the post-test, it was 80% complete (mean 8). The values before and after the test are significantly different (p-value 0.001). The socializing activities can help students learn more about the dynamics of dengue-transmitting mosquitoes and how Wolbachia bacteria can be used to control them. It is essential to create print and internet informational materials regarding dengue illness and how Wolbachia can treat it.